Assembling a thermal rhythmanalysis: Energetic flows, heat stress and polyrhythmic interactions in the context of climate change. Issue 108 (January 2020) - Oppermann, Elspeth; Walker, Gordon; Brearley, Matt
Abstract: Rhythmanalysis, as developed by Lefebvre and Regulier, has provided theoretical and methodological inspiration for a growing diversity of work in geography. We focus on the energetic liveliness and agency of rhythm to engage with heat as an energetic form and heat stress as a threat to bodily health that is becoming intensified with climate change. We deploy the analytical vocabulary of rhythmanalysis to conceptualize and empirically trace how heterogeneous, polyrhythmic interactions play out in space and time as energetic-thermal flows are variously exchanged, accumulated and dispersed within and around human bodies. At the empirical site of an 'open-cut' mine in northern Australia, where labour is physically intense, intrinsically hazardous and thermally at the threshold of embodied capacities to function, we develop a distinctive interdisciplinary analysis of rhythms of the thermal environment; rhythmic patterns in the choreography of labour and production; and corporeal rhythms in working bodies. Combining thermal physiology, ethnography and environmental monitoring methods to reveal these interacting rhythms, we identify how polyrhythmic thermal entanglements produce and shape the management of heat stress, and their significance for movements between 'eurhythmic' and ' arrhythmic ' conditions. The case study pushes these terms to their limits, so we propose 'dysrhythmic' as a new adjective for the rhythmanalytic lexicon that enables greater analytical traction on the components of polyrhythmic assemblages. Beyond the specific problem of managing heat stress, we argue there is much insight to be gained from bringing rhythmanalysis into geographical engagements with the temporalities of adaptation in a changing global climate.